A Study on Antithromin III Deficiency in Children with Extrahepatic Portal Hypertension Attending a Tertiary Care Hospital in Bangladesh (Journal of Comilla Medical College Teachers' Association, 2024)
Background: Extrahepatic portal venous obstruction accounts for 80% of cases of portal hypertension. Of all cases of portal hypertension (PHT) in developing countries, 40% are due to portal vein thrombosis. No risk factors were found in most of the cases of extrahepatic portal hypertension. To date, numerous observational studies have reported the prevalence of antithrombin III deficiency in patients with portal vein thrombosis. In Bangladesh, a largely populated country, we see a good number of patients with EHPVO every year. But there is a lack of such studies in our country about the frequency of antithrombin III deficiency.Objective: To find out the frequency of antithrombin III deficiency in children with extrahepatic portal hypertension.Methods: Over a period of 18 months, this cross-sectional descriptive study was carried out at the Department of Paediatric Gastroenterology and Nutrition of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Children of either gender diagnosed with cases of extrahepatic portal hypertension were included in this study. Informed written consent was obtained from the parent/caregiver of each child. Data were analyzed by using SPSS 22.0 for Windows 10 (SPSS, Inc, Chicago, IL). In all cases, the significance level of p value was